Fracture damage and energy evolution of fissured coal subject to triaxial unloading condition - Zhijie Zhu; Peng Wang; Xiaohan Yang; Jan Nemcik; Ting Ren; Laigui Wang; Jun Han; Songsong Guan (International Journal of Coal Science & Technology)
Abstract Fissured coal mass under triaxial unloading condition exhibits higher burst potential than the triaxial loading condition, which poses challenge to safety and productivity of resources extraction and underground space utilization. To comprehensively understand the mechanism of unloading-induced burst during excavation process, this study investigated the fracture and energy evolution of samples with different fissure types such as single, two parallel, and two coplanar-parallel using PFC2D modelling. Triaxial loading tests were conducted to determine the compressive strengths and other parameters. With increase of fissure inclination angle, the triaxial compressive strength decreases for β = 0°–30°, and then increase for β = 30°–90°. The strength of samples with two coplanar-parallel fissures is the highest. Fissure can significantly change the distribution of fracture and elastic energy. Secondary cracks were generated starting from both ends of the fissure. For β = 0°–60°, low elastic strain energy area was produced around the fissure along the loading direction. The elastic strain energy is transferred to the outside of fissures. For β = 75°–90°, only a small amount of high elastic strain energy was generated on both sides of the fissure. The fracture expansion under unloading conditions occurred due to tensile stress T caused by unloading differential rebound deformation and the shear stress on the fissure surface.